A proposed program for the training of community school teachers in Vietnam - Van, Luu Thi Kim 1936- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1966)
Based on the achievement of the Philippine Community School and the similarities in socio-economic and geographical conditions between the Philippines and Vietnam, this study proposed a teacher education program for community school teachers in Vietnam. It is patterned after selected teacher training institutions which prepare community teachers for community school in the Philippines.
Thesis (Master of Education)--University of the Philippines Diliman; 1966
Keywords: Teachers -- Training of -- Philippines; Teachers -- Training of -- Vietnam